Analisis Kesadaran Masyarakat Kota Binjai tentang Pentingnya Asuransi di PT Prudential Syariah Binjai - Siregar, Indah Kurniati; Lubis, Fauzi Arif (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study focuses on the analysis of public awareness of the city of Binjai about the importance of insurance at PT. Prudential Syariah Binjai. The purpose of this research is to provide awareness to the people of Binjai City about the importance of sharia insurance, because the products obtained by PT. Prudential Syariah Binjai is very useful for the people of Binjai City. In this research, using qualitative research methods and data collection techniques through interviews and literature review. Therefore, the results of the research show that people in Binjai City have realized how important Islamic insurance is for them, because they feel the benefits of insurance itself. .